2004
DOI: 10.1111/j.1460-9568.2004.03674.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide increases the spontaneous firing rate of rat medial vestibular nucleus neurons in vitro via a cyclic GMP‐mediated PKG‐independent mechanism

Abstract: The effects of nitric oxide (NO) on the discharge rate of medial vestibular nucleus neurons (MVNn) were investigated in rat brainstem slices. The NO-donor sodium nitroprusside (SNP, 200 microM) caused a marked enhancement (+36.7%) of MVNn spontaneous firing rate, which was prevented by the NO-scavenger, carboxy-PTIO (300 microM). The SNP effects were not modified (+37.4%) by synaptic uncoupling, suggesting that NO influences intrinsic membrane properties of MVNn rather than the synaptic input they receive. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 73 publications
3
21
0
Order By: Relevance
“…It has been reported that NO participates in numerous functions in the CNS (Bon and Garthwaite 2003;Garthwaite and Boulton 1995;Schuman and Madison 1994;Lin et al 2010;Vincent 2010;Garthwaite 2008), and its role in the regulation of neuronal excitability has been demonstrated (Centonze et al 2001;Podda et al 2004;Xu et al 1998). Indeed, NO actions in the CNS are frequently documented as modulation of ion channels (Ahern et al 2002;Grassi et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that NO participates in numerous functions in the CNS (Bon and Garthwaite 2003;Garthwaite and Boulton 1995;Schuman and Madison 1994;Lin et al 2010;Vincent 2010;Garthwaite 2008), and its role in the regulation of neuronal excitability has been demonstrated (Centonze et al 2001;Podda et al 2004;Xu et al 1998). Indeed, NO actions in the CNS are frequently documented as modulation of ion channels (Ahern et al 2002;Grassi et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Nested PCR Nested-PCR assay was performed on MVN isolated from the brainstem of 8 rats, as previously described [11]. Primers sequences were: PCR (first round), forward, 5 0 -GAT ATT AAA CTA ACC ATG AAG AC-3 0 ; reverse, 5 0 -TAA CAG CCG GTT CAA CCT GAT-3 0 (product size 816 bp) [6]; nested PCR (second round), forward, 5 0 -AGG CAC CAT GGC TCT TTT CAA T-3 0 ; reverse, 5 0 -GAA CGT CAA GTT TAA ACT GCA G-3 0 (product size 500 bp).…”
Section: Methodsmentioning
confidence: 99%
“…Recent findings by our group suggest a role for CNG channels in the modulation of medial vestibular nucleus neuron (MVNn) excitability [11]. We demonstrated that nitric oxide (NO) increases the spontaneous firing rate of MVNn via cGMP-mediated, protein kinase-independent mechanism.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…NO directly causes DRG neurons to lower their activation threshold, leading to increased hyperexcitability. Aberrant DRG activation and damage is thought to cause sensory neuronopathy, a diffuse and length-independent neuropathic pain syndrome (Zimmermann, 2001;Podda et al, 2004). Importantly, recent evidence indicates that proinflammatory cytokines, including TNFa and IL-1b, may participate in the resolution of tissue damage and recovery of nerve function (Austin and Moalem-Taylor, 2010;Nadeau et al, 2011).…”
Section: -Gly Carb Inhibits No Formation In Macrophagesmentioning
confidence: 99%